A Virtual Reality Intervention for the Treatment of Phantom Limb Pain: Development and Feasibility Results. Issue 10 (5th June 2019) - Rutledge, Thomas; Velez, Deborah; Depp, Colin; McQuaid, John R; Wong, Garland; Jones, R Carter W; Atkinson, J Hampton; Giap, Bosco; Quan, Alex; Giap, Huan
Abstract: Objective: To describe the development of a virtual reality (VR) treatment for phantom limb pain (PLP) and phantom sensations and provide feasibility data from testing the treatment in a population of veterans. Design & Subjects: Fourteen participants completed a baseline visit evaluating their amputation, PLP, and phantom sensations. Subsequently, participants completed a VR treatment modeled after mirror therapy for PLP, navigating in a VR environment with a bicycle pedaler and motion sensor to pair their cadence to a VR avatar. The VR avatar enabled visualization of the participant's intact phantom limb in motion, a hypothesized mechanism of mirror therapy. Setting: Laboratory. Methods: Participants completed pre- and post-treatment measures to evaluate changes in PLP, phantom sensations, and rate helpfulness, realism, immersion, adverse experiences, and treatment satisfaction. Results: Eight of 14 participants (57.1%) reported PLP pre–VR treatment, and 93% (13/14) reported one or more unpleasant phantom sensations. After treatment, 28.6% (4/14) continued to report PLP symptoms (t[13] = 2.7, P = 0.02, d = 0.53) and 28.6% (4/14) reported phantom sensations (t[13] = 4.4, P = 0.001, d  = 1.7). Ratings of helpfulness, realism, immersion, and satisfaction were uniformly high to very high. There were no adverse experiences. Four participants completed multiple VR treatments, showing stable improvements in PLP intensity and phantom sensations and high user ratings. Conclusions: This feasibility study of a novel VR intervention for PLP was practical and was associated with significant reductions in PLP intensity and phantom sensations. Our findings support continued research in VR-based treatments in PLP, with a need for direct comparisons between VR and more established PLP treatments.